Acute dronedarone is inferior to amiodarone in terminating and preventing atrial fibrillation in canine atria - Burashnikov, Alexander (2010)
BACKGROUND: Dronedarone is FDA approved for the treatment of patients with atrial fibrillation (AF) as a safe alternative to amiodarone. There are no full-length published papers describing the effectiveness of acute dronedarone against AF in experimental or clinical studies. METHODS: We determined the effect of acute dronedarone and amiodarone on electrophysiological parameters, and their anti-AF efficacy in canine isolated arterially-perfused right atria. Transmembrane action potentials and pseudo-ECGs were recorded. Acetylcholine (ACh, 1.0 μM) was used to induce persistent AF. RESULTS: Amiodarone-induced changes were much more pronounced than those of dronedarone on a) action potential duration (ΔAPD(90), +51±17 vs. 4±6 ms, p>0.01), b) effective refractory period (ΔERP +84±23 vs. 18±9 ms, p<0.001), c) diastolic threshold of excitation (ΔDTE, +0.32±0.11 vs. 0.03±0.02 mA, p<0.001), and d) V(max) (ΔV(max):−43±14 vs. −11±4%, p<0.01, n=5–6; all recorded at 10 μM, CL = 500 ms). Persistent AF was induced in 10/10 atria exposed to ACh alone; subsequent addition of dronedarone or amiodarone terminated AF in 1/7 and 4/5 atria, respectively. Persistent ACh-mediated AF was induced in 5/6 and 0/5 atria pretreated with dronedarone and amiodarone, respectively. CONCLUSIONS: The electrophysiological effects and anti-AF efficacy of acute dronedarone are much weaker than those of amiodarone in a canine model of AF. The efficacy of acute dronedarone to prevent induction of acetylcholine-mediated AF as well as to terminate persistent AF in canine right atria is relatively poor. Our data suggest that acute dronedarone is a poor substitute for amiodarone for acute cardioversion of AF or prevention of AF recurrence.